The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.4049/jimmunol.2200308
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP Induces Novel Nectin-2+ (CD112+) Neutrophils to Promote Th1 Differentiation in Sepsis

Abstract: Neutrophil heterogeneity represents different subtypes, states, phenotypes, and functionality of neutrophils implicated in sepsis pathobiology. Extracellular cold-inducible RNA-binding protein (eCIRP) is a damage-associated molecular pattern that promotes inflammation and alters neutrophil phenotype and function through TLR4. Nectin-2 or CD112 is an Ig-like superfamily member. CD112 serves as the ligand for DNAM-1 (CD226), which induces Th1 differentiation in naive CD4+ T cells. Th1 cells produce IFN-γ to fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
0
1
1
Order By: Relevance
“…It is also meaningful to evaluate the molecules and pathways related to cell death simultaneously to grasp the mechanisms of cellular aging from a wider perspective. Our previous studies revealed several novel subtypes of neutrophils, including APANs, nectin-2, and serpin B2 neutrophils, which were found to be upregulated during sepsis (9,10,33). However, our latest scRNA-seq data could not distinctly demonstrate these specific neutrophil subtypes.…”
Section: B Acontrasting
confidence: 60%
“…It is also meaningful to evaluate the molecules and pathways related to cell death simultaneously to grasp the mechanisms of cellular aging from a wider perspective. Our previous studies revealed several novel subtypes of neutrophils, including APANs, nectin-2, and serpin B2 neutrophils, which were found to be upregulated during sepsis (9,10,33). However, our latest scRNA-seq data could not distinctly demonstrate these specific neutrophil subtypes.…”
Section: B Acontrasting
confidence: 60%
“…Наше дослідження показало значне підвищення вмісту IFN-γ через 10 діб після хірургічного моделювання ушкоджень м'яких тканин. Ймовірно, це обумовлено запальними процесами, що продовжувались у глибоких шарах ранового каналу, адже відома здатність цього цитокіну стимулювати активність нейтрофілів і макрофагів [8,11]. Запальна фаза у репаративних процесах має ключове значення для успішного загоєння ушкоджень, завдяки ефективному усуненню інфекційних агентів і залишків некротизованих тканин [12].…”
Section: гістологічна характеристикаunclassified